2019
DOI: 10.1111/aogs.13682
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the disengagement of the forceps on levator ani muscle injuries in instrumental delivery: A multicenter study

Abstract: Introduction Forceps use is the main risk factor for levator ani muscle (LAM) injuries. We believe that the disengagement of the forceps branches before delivery of the fetal head could influence LAM injuries, so we aimed to determine the influence of the disengagement of the forceps on the occurrence of LAM avulsion during forceps delivery. Material and methods A prospective, observational, multicenter study was conducted with 261 women who underwent forceps delivery. The women were classified according to wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
5
1
Order By: Relevance
“…Five studies were retrospective and the rest prospective. The ultrasound examination was performed in most studies within 6 months after delivery [11][12][13][14][15][16][17]19,20,22,23,[25][26][27][28][29][30][31][32][33][34][35], though some performed an ultrasound examination only or also after this period [17,18,21,24,35,36]. Some papers included a small number of VDs [12,20,27] and FDs [12][13][14]27], a possible source of bias.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Five studies were retrospective and the rest prospective. The ultrasound examination was performed in most studies within 6 months after delivery [11][12][13][14][15][16][17]19,20,22,23,[25][26][27][28][29][30][31][32][33][34][35], though some performed an ultrasound examination only or also after this period [17,18,21,24,35,36]. Some papers included a small number of VDs [12,20,27] and FDs [12][13][14]27], a possible source of bias.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of articles that specified the type of vacuum used in the RV reported that a metal vacuum bird's cup was 50 mm [19,[24][25][26]29,30,[32][33][34], although one of them also assessed LAM avulsion after a Kiwi vacuum was used [32]. The majority of studies on FD described the rates of LAM avulsion with Kielland's forceps [28][29][30][31]33,34,36], though one of them studied Anderson forceps and Wrigley forceps [19].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations